Effects of infield rainwater harvesting methods and organic manure in improving soil chemical properties and maize production in low rainfall area of Zimbabwe - Andrew Tapiwa Kugedera; Letticia Kudzai Kokerai (Cogent Food & Agriculture)
Maize production has been declining in many smallholder farming systems because of soil moisture stress due to declining soil fertility. The aim of this study was to evaluate the effects of combining infiltration and planting pits with organic nutrient sources in improving soil chemical properties and maize yields in low-rainfall areas of Zimbabwe. The experiment was arranged in a split-split plot in a randomized complete block design, in which three rainwater harvesting methods (infiltration pits (IP), infiltration + planting pits (IP + P), and conventional tillage) were used as the main plot factor. The sub-plots used were goat manure at 5 t ha−1, 5 t ha−1 of cattle manure + compost, and no organic amendment (control). Two maize varieties (SC529 and PAN413) were used as sub-sub plot factor. Total nitrogen, exchangeable calcium and magnesium were improved with application of cattle + compost manure. Results showed that the main treatments had significant effects (p ≤ 0.05) on maize production. Infiltration + planting pits had a significantly higher (p ≤ 0.05) maize grain yield than infiltration pits and conventional tillage. Maize grain yields were also significantly influenced (p ≤ 0.05) by the application of cattle manure + compost compared to goat manure at the same rate. Integrating rainwater harvesting and nutrient management improved the maize grain yield. It can be concluded that the use of IP + P integrated with cattle manure + compost improves maize yields in smallholder farming environments in semi-arid areas and achieves food security.